2024
DOI: 10.1002/1878-0261.13646
|View full text |Cite
|
Sign up to set email alerts
|

TACE inhibition: a promising therapeutic intervention against AATF‐mediated steatohepatitis to hepatocarcinogenesis

Akshatha N. Srinivas,
Diwakar Suresh,
Prashant M. Vishwanath
et al.

Abstract: Metabolic dysfunction‐associated steatohepatitis‐driven hepatocellular carcinoma (MASH‐HCC) is a global clinical challenge for which there is a limited understanding of disease pathogenesis and a subsequent lack of therapeutic interventions. We previously identified that tumor necrosis factor‐alpha (TNF‐α) upregulated apoptosis antagonizing transcription factor (AATF) in MASH. Here, we investigated the effect of TNF‐α converting enzyme (TACE) inhibition as a promising targeted therapy against AATF‐mediated ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Of note, green jackfruit flour differs significantly from the placebo in its dietary fiber composition [20] and it is also evident that unripe jackfruit has a higher fiber content when compared to ripe jackfruit [45]. Dietary fibers, encompassing a variety of plant-derived carbohydrates resistant to digestion by human enzymes, play a pivotal role in MASLD management [46].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, green jackfruit flour differs significantly from the placebo in its dietary fiber composition [20] and it is also evident that unripe jackfruit has a higher fiber content when compared to ripe jackfruit [45]. Dietary fibers, encompassing a variety of plant-derived carbohydrates resistant to digestion by human enzymes, play a pivotal role in MASLD management [46].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies revealed the role of AATF in impeding HCC angiogenesis by downregulating PEDF (24). Recently, we investigated the role of AATF in MASH-HCC and showed that TACE inhibition by Marimastat prevents AATF-mediated inflammation, fibrosis, and oncogenesis (27). In the current study, we identified for the first time the role of AATF in lipid metabolism and its implications in the development of MASH.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also demonstrated the inhibitory effects of curcumin on MASH-HCC by downregulating AATF via the KLF4-SP1 pathway (26). We recently explored the involvement of the SIRT1-TIMP3-TACE axis in AATF upregulation, with subsequent TACE inhibition leading to AATF downregulation and attenuation of MASH-associated liver tumorigenesis (27). However, the mechanistic role of AATF in the pathophysiology of MASH remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%